STRATEGI ADAPTASI TERHADAP LINGKUNGAN MINIM OKSIGEN MELALUI GAMBARAN ANATOMI ORGAN RESPIRASI KELELAWAR DI KARST GUDAWANG BOGOR - Wijayanti, Fahma (El-Hayah : Jurnal Biologi, 2013)
The existence of cave dwelling bats of karst area need to be conserved, because bats have important roles for the ecosystem both inside the cave  as well as outside the cave. The purpose of  this study was to observe  structural respiratory adaptation of the cave bats . This study was conducted from July 2013 to November  2013 at three caves in  Karst  Gudawang, Bogor Regency, West Java. In each cave where the bats roosting, the temperature, also the humidity, and  oxygen level were measured. Samples were caught from every bat roost during the day when the bats were staying in their roosts.  Lungs and trachea  removed from body and  were  made preparations for histology. The lung and trachea  was observed under the microscope. The data were analyzed using ANOVA. The result showed:  The ratio of  lung weight/body weight  increased by the decrease of oxygen levels. This tendency also revealed  in diameter of trachea/body weight  change